Corporate Sustainable performance and profitability : Exploring The Moderating Role of Liquidity and Stock Volatility in Egypt \ - Nada Salah Hussein Mahmoud Elgabry; Doaa Salman Abdo; Asmaa Hamdy (Giza : MSA University (3;s, 2024)
the purpose of this study is to investigate whether corporate sustainable performance CSP impacts the film profitability by exploring the moderating role of liquidity and stock volatility in Egypt
A thesis submitted in the partial fulfilment of the degree of master of sciences MSC in Business Administration
Keywords: Management; Business Administration; sustainability; profitability; Environmental performance